An Analysis of Slang in the Song "Collide" Sung by Justien Skye - Ordin, Ferdinandus; Sene, Chamelya Vivi Crystanty; Pale, Erlinda Sonya; Angket, France Melkianus; Bria, Anggelina Leonarda; Neno, Priskilla (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2023)
Slang is considered a really casual word or expression that can be used in a song to make it more enjoyable and entertaining. Thus, the main purpose of the study was to find out the meaning of slang and to discover the sorts of slang within the verses of Justine Skye's melody "Collide". Qualitative descriptive was the design utilized in the present study. The strategy and centre on substance investigation were utilized in analyzing the information. The examination begins from February 2023 to March 2023. The outcomes of this conducted study informed that the slang word in Justine Skye's melody comprises of a few word arrangements mentioned as 8 clippings, 3 mixings, and 2 coinages. Based on the results of the study, clipping was the most common slang found in Justine Skye's tunes.